(untitled) (Lex localis - Journal of Local Self-Government, 2024)
The growth of democratic societies depends on strong local administrations. Local governments are more likely to “create systems of governance that are successful and responsible to local people” than central governments because they are typically more responsive to local needs and ambitions. India and Kenya have adopted local self-government at different levels to fulfill development goals. However, some common causes like, Paucity of funds, lack of planning, unplanned urbanization, excessive state control, etc. are some problems that resulted urban local government are evolved as inefficient and substandard governance. The purpose of this paper is to comparatively analyze urban local government structures in India and Kenya as well as challenges before it. This assessment is based on data collected from some Indian states like Karnataka, Andhra Pradesh, Arunachal Pradesh, and Nairobi, Kisumu and Mombasa from Kenya. The findings of this study show that urban local governments in India and Kenya continue to remain plagued by numerous problems, which affect their performance in the efficient discharge of their duties.